2002
DOI: 10.1002/psc.409
|View full text |Cite
|
Sign up to set email alerts
|

New potent hGH‐RH analogues with increased resistance to enzymatic degradation

Abstract: Four hGH-RH analogues containing homoarginine (Har) and/or D-Arg were obtained by solid-phase methodology using Boc-chemistry. To introduce Har residues, a Lys(Fmoc) protected Lys derivative was incorporated in the appropriate positions (11, 12, 20, 21 or 29): after assembly of the peptide chain the Fmoc group was removed and the peptide-resin was guanidinylated by treatment with N,N'-bis(tert-butoxycarbonyl)-S-methylisothiourea. The peptides were cleaved from the resin by treatment with liquid HF, and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…All the amino acids and reagents for peptide synthesis were obtained from Sigma Chemical Co. (St Louis, MO, USA), Fisher Scientific (Fair Lawn, NJ, USA), Bachem (Bubendorf, Switzerland), Ferak Berlin (Berlin, Germany), Aldrich (Steinheim, Germany) and IRIS Biotech (Marktredwitz, Germany). N , N ′‐Di‐ tert ‐butoxycarbonyl‐1 H ‐benzotriazole‐1‐carboxamidine (Boc 2 CABt) and N , N ′‐Di‐ tert ‐butoxycarbonyl‐1‐methyl‐2‐thiourea were synthesized as described previously10, 11. Thin layer chromatography (TLC) was performed on Merck F 254 and Silufol plates using specified solvent system.…”
Section: Methodsmentioning
confidence: 99%
“…All the amino acids and reagents for peptide synthesis were obtained from Sigma Chemical Co. (St Louis, MO, USA), Fisher Scientific (Fair Lawn, NJ, USA), Bachem (Bubendorf, Switzerland), Ferak Berlin (Berlin, Germany), Aldrich (Steinheim, Germany) and IRIS Biotech (Marktredwitz, Germany). N , N ′‐Di‐ tert ‐butoxycarbonyl‐1 H ‐benzotriazole‐1‐carboxamidine (Boc 2 CABt) and N , N ′‐Di‐ tert ‐butoxycarbonyl‐1‐methyl‐2‐thiourea were synthesized as described previously10, 11. Thin layer chromatography (TLC) was performed on Merck F 254 and Silufol plates using specified solvent system.…”
Section: Methodsmentioning
confidence: 99%
“…There is a great demand for more stable analogues which would allow a reduction in dose and frequency of administration. Numerous analogues of hGH-RH-(1-29)-NH 2 have been synthesized and tested in a search for peptides of increased metabolic stability and potency [4][5][6]. hGH-RH-(1-29)-NH 2 itself is rapidly metabolized in plasma, as a result of Ala 2 -Asp 3 peptide bond cleavage by dipeptidylpeptidase IV with the formation of an inactive 3-29 fragment [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently several biologically active analogues containing side-chain extended homoarginine (Har) instead of Arg and Lys were described. It was found that peptide bonds formed by the carboxyl group of Har are completely stable to trypsin [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many agonistic and antagonistic analogs of GHRH, based on the shortest bioactive sequence of hGHRH(1-29)NH 2 , have been synthesized to elucidate the structure-activity relationships and to increase their biological activity (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The first reported GHRH antagonist, termed herein as the ''standard antagonist,'' has the chemical structure of [Ac-Tyr 1 , D-Arg 2 ]hGHRH(1-29)NH 2 (7).…”
mentioning
confidence: 99%